Task Sensitivity in L2 English Speakers’ Syntactic Processing: Evidence for Good-Enough Processing in Self-Paced Reading - Tan, Maryann; Foltz, Anouschka (Frontiers in Psychology, 2020)
Native (L1) and second-language (L2) sentence processing can sometimes be shallow. A Good-Enough approach suggests that speakers may engage in shallow processing if the task permits. This study tests English native speakers and native Chinese L2 learners of English to explore whether different task demands affect their sentence processing. In a self-paced reading task, participants read globally or temporarily ambiguous sentences with relative clauses preceded by a matrix clause containing two noun phrases (NPs). Comprehension questions modulated task difficulty: Half the participants received comprehension questions that probed their interpretation of the relative clauses whereas the remaining half received superficial questions unrelated to the relative clauses. Task difficulty affected reading times at the point of disambiguation for both L1 and L2 participants. Additionally, participants’ attachment choices for globally ambiguous sentences were consistent with reading times of the disambiguating region in both L1 and L2 readers. The results suggest that both L1 and L2 syntactic processing is modulated by the task at hand. We argue for a similar treatment of shallowness for L1 and L2 speakers in models of sentence processing, along the lines of the Good-Enough approach to language processing.